Use of the sampling method in the tax examination procedures when applying the self-assessment system in taxation An Empirical Study of the General Commission for Taxes - األسخاذ امدکخِر وحىد حنِ داود امخرسان; األسخاذ امىساغد امدكخِر غالء فريد غتد االحد; امىدرسث امىساغدة خٌساء ًاضر حسيي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
It is well known to all that the contribution of tax revenues within the revenues of the general budget is very little and does not exceed 6%, despite the importance of tax revenues in the public revenues of most countries, including those countries whose oil is the main source of revenue. Most countries in the world and developed countries in particular Methods of estimation and taxation, and those advanced methods to adopt self-assessment system in tax accounting. Self-assessment is the way in which the tax administration grants the taxpayer’s legal right to pay the tax by calculating the tax that is incurred and determines the amount he pays or the amount he has the right to recover. The self-assessment simply means that the taxpayer pays his tax on the basis of what his accounts show and what he shows in his tax declaration of net income. Tax administration only accepts this at this stage, but the tax administration has the right to choose certain persons and call them to check their books and all their financial documents To ensure that their account is correct for the tax paid. If the calculation of the tax paid is not correct or the books and documents show that other income not declared by the person in his declaration then the tax will be properly refunded with the fine and possibly other penalties in countries of imprisonment for years. This method must be controlled by the tax administration on the activities and activities of the taxpayer during the period or periods. The researchers believe that the determination of the size and number of taxpayers subject to tax examination by the Commission should be studied scientifically and objectively using the sampling method As a scientific means contributing to the provisions of the Authority’s control over the taxpayer’s activities and financial activities with a view to determining taxable income and accounting for it. In order to achieve the objectives of the research will discuss the following axes to represent the general framework of research: - Self-assessment system in taxation. - Method of sampling in the tax examination